Tctp, a unique Ing5-binding partner, inhibits the chromatin binding of Enok in Drosophila. - Kim, L.H.; Kim, J.Y.; Xu, Y.Y.; Lim, M.A.; Koo, B.S.; Kim, J.H.; Yoon, S.E.; Kim, Y.J.; Choi, K.W.; Chang, J.W.; Hong, S.T. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
The MOZ/MORF histone acetyltransferase complex is highly conserved in eukaryotes and controls transcription, development, and tumorigenesis. However, little is known about how its chromatin localization is regulated. Inhibitor of growth 5 (ING5) tumor suppressor is a subunit of the MOZ/MORF complex. Nevertheless, the in vivo function of ING5 remains unclear. Here, we report an antagonistic interaction between Drosophila Translationally controlled tumor protein (TCTP) (Tctp) and ING5 (Ing5) required for chromatin localization of the MOZ/MORF (Enok) complex and H3K23 acetylation. Yeast two-hybrid screening using Tctp identified Ing5 as a unique binding partner. In vivo, Ing5 controlled differentiation and down-regulated epidermal growth factor receptor signaling, whereas it is required in the Yorkie (Yki) pathway to determine organ size. Ing5 and Enok mutants promoted tumor-like tissue overgrowth when combined with uncontrolled Yki activity. Tctp depletion rescued the abnormal phenotypes of the Ing5 mutation and increased the nuclear translocation of Ing5 and chromatin binding of Enok. Nonfunctional Enok promoted the nuclear translocation of Ing5 by reducing Tctp, indicating a feedback mechanism between Tctp, Ing5, and Enok to regulate histone acetylation. Therefore, Tctp is essential for H3K23 acetylation by controlling the nuclear translocation of Ing5 and chromatin localization of Enok, providing insights into the roles of human TCTP and ING5-MOZ/MORF in tumorigenesis.